(untitled) (Research, Society and Development, 2020)
This study aimed to describe the triggering aspects of leprosy on psychological distress, highlighting the coping actions from the perspective of the nurse. This is a descriptive and exploratory bibliographic review, carried out in the databases of the electronic portal Virtual Health Library (VHL), from August to September 2020. The repercussions of the diagnosis of leprosy are directly related to the mode of live and socialize, since the sociocultural representations about the disease have repercussions on stigma and prejudice, triggering psychological suffering with changes in self-esteem and self-image. In this context, the decentralized actions of the nurse on the implementation of actions of education, promotion and prevention in health are highlighted, stimulating self-care and better adherence to the health-disease process. The need to further discuss psychic care for patients diagnosed with leprosy and its socio-cultural representations is emphasized, since patient-disease praxis goes beyond the physical scope, needing to strengthen health promotion in this line of care.